Business plans handbook. Volume 26 a compilation of business plans developed by individuals throughout North America - Hill, Sonya D.; Gale (Firm) (Detroit, Mich. : Gale, 2013)
Actual business plans compiled by, and aimed at, entrepreneurs seeking funding for small businesses. Presents sample plans taken from businesses in the manufacturing, retail and service industries which serve as examples of how to approach, structure and compose business plans.
Airport shuttle : Prestige Car Service -- Baby furniture rental : Baby, Baby -- Banquet facility : Sycamore Hills Banquet Center -- Catering service : Creative Catering -- Children's hair salon : Kool Kidz -- Consignment shop : Upscale Resale -- Copy shop : Pronto Printing -- Custom paint and body shop/classic car restorations : Racing Stripes -- Dance studio : Dancing Divas -- Dollar store : Dollar Daze -- Food truck : Suerte Cuban Cuisine -- General staffing company : GENRX LLC -- Gift basket service : Sunrise Gift Baskets -- Handmade writing instruments & accessories business : StanMark Gifts Inc. -- Hedge fund : Oxford Advisors -- Home accessibility services provider : AccessibilityWorx Inc. -- Paintball store and field : X-Treme Paintball -- Real estate investment company : Schroeder Real Estate -- Resume writing business : Nieberger Career Consulting, LLC -- Solar panel isntallation service : Living Green Energy Services.
"ISSN 1084-4473."
Includes index.
Description based on print version record.
Keywords: Small business -- Planning -- Handbooks, manuals, etc; Business planning -- Handbooks, manuals, etc; Small business -- Planning -- Information services -- Directories; New business enterprises -- Handbooks, manuals, etc; Entrepreneurship -- Handbooks, manuals, etc